If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -5 = 3 + -9(y + 2) Reorder the terms: -5 + y = 3 + -9(y + 2) Reorder the terms: -5 + y = 3 + -9(2 + y) -5 + y = 3 + (2 * -9 + y * -9) -5 + y = 3 + (-18 + -9y) Combine like terms: 3 + -18 = -15 -5 + y = -15 + -9y Solving -5 + y = -15 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. -5 + y + 9y = -15 + -9y + 9y Combine like terms: y + 9y = 10y -5 + 10y = -15 + -9y + 9y Combine like terms: -9y + 9y = 0 -5 + 10y = -15 + 0 -5 + 10y = -15 Add '5' to each side of the equation. -5 + 5 + 10y = -15 + 5 Combine like terms: -5 + 5 = 0 0 + 10y = -15 + 5 10y = -15 + 5 Combine like terms: -15 + 5 = -10 10y = -10 Divide each side by '10'. y = -1 Simplifying y = -1
| 7y-2(8y+1)=9 | | 3a+(2a-5)=13-2(a-2) | | 4x-7+5x=11 | | 21X^2+32X=5 | | 3k+16=7k+4 | | .75*x=6 | | 2+4x+3x=44 | | 21X^2= | | 6p+8=11+5p | | -4r=4r+21 | | 7-6x=-38 | | 2y+7x=350 | | -62-9= | | 19m+7-3(4m+0)=448 | | 10x+14=5x+139 | | -7x+10-x=42 | | 7x^2+26x*15= | | 4x+15.5=41.5 | | .66*x=12 | | (5x-7)=(4x+11) | | -5+6+x=23 | | 2x+4-2=5x-3 | | 66*x=12 | | 9.8+y=-87.6 | | 5=12+4x-5x | | 3x+2=7x+-5 | | .66*16=x | | 7(x-3)=2(3+8) | | 4x+1=11x+8 | | 2+5x+6x=2 | | 1-2x+5=4x+6 | | 1.3x-2.39+5.76x=4.74 |